Quantum Chemical Studies of Porphyrin- and Expanded Porphyrin-Based Systems and Their Potential Applications in Nanoscience. Latin America Research Review - Cardenas-Jiron, G; Mera-Adasme, R; Borges-Martinez, M; Pino-Rios, R (John Wiley and Sons Inc., 2019)
Porphyrins and expanded porphyrins are fascinating molecular structures, and its wide applicability in different fields of the nanoscience has produced an extensive number of scientific publications. The purpose of this article is to review the research performed on porphyrins and expanded porphyrins in the Latin American region at a theoretical level of quantum chemistry using different methodologies available. The present review is organized considering the most important applications that these molecular systems have found. In this way, we classify the reported works in the following fields studied by the nanoscience: molecular electronics, dye-sensitized solar cells, and photodynamic therapy. Because of its relevance, we also highlight other reports focused on the topological analysis of the electron density and aromaticity. Current investigation on these topics applied to porphyrin- and expanded porphyrin-based systems and the future perspective in this field are presented. © 2018 Wiley Periodicals, Inc.